Comparison of peak oxygen consumption during cycle and treadmill exercise in severe chronic obstructive pulmonary disease. Issue 8 (August 1995) - Mathur, R S; Revill, S M; Vara, D D; Walton, R; Morgan, M D
Abstract : BACKGROUND–In normal subjects treadmill exercise usually produces the greatest maximal oxygen consumption (VO2max). This may not be true for patients with severe chronic obstructive pulmonary disease (COPD) in whom bicycle exercise, which offers support for the shoulder girdle, may produce a higher oxygen consumption than treadmill exercise. The aim of this study was to determine which mode of exercise produced the greatest oxygen consumption in patients with severe COPD. METHODS–Eight patients with severe COPD (forced expiratory volume in one second (FEV1) more than three standardised residuals below predicted) exercised to a symptom limited maximum on a bicycle and on a treadmill on separate days. The workload on the bicycle wa increased by 10 watts each minute, and the treadmill gradient was increased by 2.5% alternate minutes whilst the speed remained constant. Measurements of oxygen consumption (VO2), ventilation (VE), heart rate, and oxygen saturation were made, and capillary blood gases were measured before and immediately after exercise. Lactate concentration was measured before and four minutes after exercise. RESULTS–There were no differences at peak exercise between the two forms of exercise for VO2 (median 11.7 and 12.2 ml/min/kg for bicycle and treadmill, respectively), for VE (median 26.6 and 25.0 l/min, respectively), and for heart rate (median 119 and 115 beats/min, respectively). The median lactate levels after bicycle exercise were higher than those after the treadmill (2.42 v 0.94 mmol/l). CONCLUSIONS–Although only a small number of patients was studied and individual variability was large, there was no clear difference between the two forms of exercise. Regular bicycle exercise was unfamiliar to this group of patients and generated the greatest lactate response. The results do not support the hypothesis that bicycle exercise will produce a better performance in patients with severe COPD, but the two modes of exercise cannot be used interchangeably.